Multiteam systems : an organization form for dynamic and complex environments - Zaccaro, Stephen J.; Marks, Michelle A.; DeChurch, Leslie A. (New York : Routledge, 2011)
'This book examines an emerging organizational form called the multi-team system (MTS). This type of aggregation is being increasingly adopted by organizations and agencies that need to respond to complex strategic problems. There has been increasing interest in MTSs over the last decade to the point where there is now a need to (a) describe these organizational forms more fully, (b) build conceptual frames that can guide research, and (c) begin developing tools to improve the study of MTSs. The purpose of this book is to respond to these needs. The book contains a series of chapters that expand prior conceptual frames of MTSs, defining in more detail the compositional and linkage attributes that characterize such units. The book also explores how such systems emerge and develop, as well as the methods for studying MTSs. The intent of the book is to establish and nurture a strong conceptual and methodological foundation that can guide research and practice with MTSs. Because the notion of MTSs cuts across multiple domains, this book will interest scholars in industrial/organizational psychology, organizational science, management and organizational theory, human factors, sociology, organization communications, and public administration'--
'1 Multiteam Systems: An Introduction Stephen J. Zaccaro George Mason University Michelle A. Marks George Mason University Leslie A. DeChurch University of Central Florida Over the last 2 decades, the operating work environment has become exceedingly more challenging and complex (Ilgen & Pulakos, 1999). To wit, communication and information technology has grown exponentially, increasing the pace, scope, and scale of work (Hesketh & Neal, 1999). Such technology has also increased the globalism and geographic dislocation of organizational work (Ireland & Hitt, 1999). Because of the global reach of today's business, and the increasing immediacy afforded by current technology, strategic issues, problems, and implications have greater interconnectivity across organizational boundaries. Traditional organizational forms have been typically insufficient to respond effectively to such changes. Accordingly, a number of different organizational forms that complement more conventional structures have emerged, including matrix and virtual organizations, as well as cross-functioning and ad hoc project teams'--
Includes bibliographical references and index.
Keywords: Teams in the workplace; Teams in the workplace -- Management; Leadership; Organizational effectiveness; PSYCHOLOGY / Applied Psychology; PSYCHOLOGY / Industrial & Organizational Psychology; BUSINESS & ECONOMICS / Leadership